"The Black Tile in the Mosaic": Austin Chesterfield Clarke and the Canadian Literary Tradition. Issue 1 (2nd January 2019) - Beckford, Sharon Morgan
ABSTRACT: This paper engages selected moments in Austin Clarke's literary journey to argue that in spite of his involvement in the development of Canadian literature (CanLit) during the 1960s and 1970s, the Canadian literary establishment continues to pay little critical attention to his contributions. This lack of recognition is specifically evident in recent writings about Canadian literature and the literary figures who spearheaded its development after Canada's Multiculturalism policy of 1971. Canada's becoming officially multicultural required a new narrative of Canada and new literary depictions of Canadians in their national literature, as ethnically diversified but of a single citizenship. I argue that Clarke's legacy as a Black writer should be given more prominence in Canadian institutions because today this legacy is under threat of erasure as the number of Canadian Black voices telling mainstream stories about Black people's experiences is evidently in decline.